Pengaruh Sistem Pengendalian Internal dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan - Amalia Nurul Arifah; Hendriyana Hendriyana; Qur’ani Noor (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of the Internal Control System and Human Resource Competence on the Quality of Financial Statements in a manufacturing company located in Bandung. The research focuses on examining how the effectiveness of internal control and the capability of human resources contribute to producing reliable and standards-compliant financial reports. This study employs a quantitative approach with an associative research design. The sample consists of 35 employees involved in the preparation of financial statements, selected using purposive sampling. Data were collected through questionnaires and analyzed using SPSS version 26 through multiple linear regression, t-test, F-test, and coefficient of determination analysis. The results show that the Internal Control System has a significant effect on the Quality of Financial Statements, while Human Resource Competence has no significant effect. Simultaneously, both variables have a significant effect, with an R² value of 0.632, indicating that 63.2% of the variation in Financial Statement Quality is explained by these independent variables.